PENGARUH LAMA WAKTU ENSILASE RUMPUT GAJAH YANG DIBERI MOLASES ATAU LUMPUR KECAP TERHADAP FERMENTABILITAS DAN KECERNAAN IN VITRO - Iman Hernaman; Lukman Purwanto; Handi Burhanuddin; Atun Budiman; Budi Ayuningsih; Tidi Dhalika (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
This study aimed to evaluate in vitro of Elephant grass silage using molasses and soy sauce sludge as additives with different length of ensilage. This research was conducted experimentally using a completely randomized design (CRD) with eight treatments and three replications. The data collected was carried out by variance and Duncan's test. The elephant grass is carried out by the ensilage process using molasses and soy sauce sludge additives as much as 5% with an incubation time of 3, 6, 9, and 12 weeks. The results showed that the incubation time resulted in the concentration of volatile fatty acids, dry matter, and organic matter digestibility which were significantly different (P <0.05), but not the ammonia (N-NH3) concentration. The use of soy sauce sludge additive resulted in higher volatile fatty acid and dry matter and organic matter digestibility compared to the use of molasses with the average volatile fatty acids (139.21 vs 102.92 mM), dry matter digestibility (73.34 vs 69.18%), and organic matter digestibility (66.47 vs 61.74%). The use of 5% soy sauce sludge with an ensilage duration of 12 weeks resulted in the highest average of volatile fatty acids and dry matter and organic digestibility, respectively, namely 150.67 mM, 76.10%, and 69.26%. In conclusion, the use of soy sauce sludge as much as 5% and 12 weeks of ensilage in making elephant grass silage resulted in the best fermentability and digestibility.